Responsif Bokashi Kotoran Sapi dan POC Bonggol Pisang terhadap Pertumbuhan Produksi Bawang Merah (Allium ascalonicum L.) - Tharmizi Hakim; Sukma Anandari (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2019)
The purpose of this study was to determine the responsiveness of cow dung bokashi and POC banana weevil to the growth of onion production (Allium ascalonicum L.). This research was conducted on purwo road in Sunggal sub-district, Deli Serdang district. The chosen model to carry out research using a factorial randomized group (RBD) consists of 2 factors with 16 combinations and 2 replications. The first treatment is bokashi cow dung with 4 parts namely K0 = 0 kg / plot, without K1 = 13 kg / plot, k2 = 4 kg / plot, and K3 = 6 kg / plot, second aid POC banana weevil includes of 4 parts , ie P0 = 0 cc / l water / plot, P1 = 150 cc / l water / plot, P2 = 300 cc / l water / plot and P3 = 450 ml / l water / plot. The parameters collected in this study were the number of sample leaves (strands), wet tuber sample production (grams), dry tuber production plot (grams), conversion of per hectare onion production (kg). The results of the study show that the parameters of the number of leaf samples (strands) give a real picture, the parameters of the production of wet tubers of samples (grams), production of dried plots tubers (grams) and parameters of conversion of production per hectare (kg) of red salt interaction parameters do not influence of all.